Palmar skin conductance variability and the relation to stimulation, pain and the motor activity assessment scale in intensive care unit patients - Günther, Anders C (BioMed Central, 2013)
INTRODUCTION: Many intensive care unit (ICU) patients describe pain and other adverse feelings that may impact long-term psychological morbidity. Sympathetically mediated palmar skin conductance variability is related to emotionally induced perspiration and correlates with pain levels in the perioperative setting but has not been studied in ICU patients. METHODS: Twenty non-intubated and 20 intubated general ICU patients were included in this observational study. Patients were monitored with the MED-STORM Pain Monitoring System(®). The number of skin conductance fluctuations per second (NSCF) was measured in parallel with bedside observation during one hour of intensive care, including rest, procedures and patient-staff interactions. Arousal-agitation level was monitored with the motor activity assessment scale (MAAS). Pain was monitored with the numeric rating scale (0 to 10) in patients able to communicate or by observation in patients unable to communicate. RESULTS: In non-intubated patients, NSCF increased with increasing stimulation/pain but also with higher MAAS (P = 0.002). An interaction effect was found, with increased NSCF response to stimulation/pain with increasing MAAS (P < 0.001). In intubated patients, NSCF increased significantly with increasing stimulation/pain (P < 0.001). In contrast to non-intubated patients, no difference in NSCF between MAAS levels was found for any given degree of stimulation in intubated patients. CONCLUSIONS: In critically ill patients, NSCF may be more useful evaluating emotional distress rather than pain alone. It needs to be assessed whether NSCF monitoring is clinically useful and whether controlling emotional distress with the aid of such monitoring may impact on patient care and outcomes.